Climate-sensitive health counselling: a scoping review and conceptual framework - Quitmann, Claudia; Griesel, Silvan; Schwerdtle, Patricia; Danquah, Ina; Herrmann, Alina (The lancet. Planetary health, 2023)
Health professional societies and researchers call for the integration of climate change into health counselling. However, the scientific evidence and conceptual grounding of such climate-sensitive health counselling (CSHC) remains unclear. We conducted a scoping review identifying scientific articles on the integration of climate change into communication between health professionals and patients in health-care settings. Scientific databases (Web of Science, PubMed, and Google Scholar) were searched from inception until Nov 30, 2022. 97 articles were included, of which 33 represented empirical research, and only two evaluated the effects of CSHC. More than half of the articles originated from the USA and addressed physicians. We introduce a conceptual framework for CSHC, which elaborates on aims, content areas, and communication strategies, and establishes the guiding principle of integrating CSHC into routine activities of health care. This framework supports health professionals in implementing CSHC and enables researchers to conceptualise intervention studies investigating how CSHC can contribute to the health of patients and the planet.